Correction: Controllable poly-crystalline bilayered and multilayered graphene film growth by reciprocal chemical vapor deposition. Issue 28 (2nd July 2015) - Wu, Qinke; Jung, Seong Jun; Jang, Sung Kyu; Lee, Joohyun; Jeon, Insu; Suh, Hwansoo; Kim, Yong Ho; Lee, Young Hee; Lee, Sungjoo; Song, Young Jae
Abstract : Correction for 'Controllable poly-crystalline bilayered and multilayered graphene film growth by reciprocal chemical vapor deposition' by Qinke Wu et al., Nanoscale, 2015, 7, 10357–10361.